Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 3—Redescription of Centrophorus uyato (Rafinesque) with a discussion of its complicated nomenclatural history - White, William T.; Guallart, Javier; Ebert, David A.; Naylor, Gavin J.p.; Veríssimo, Ana; Cotton, Charles F.; Harris, Mark; Serena, Fabrizio; Iglésias, Samuel P. (Zootaxa, 2022)
Centrophorus uyato (Rafinesque, 1810) has a complicated nomenclatural history which has led to multiple scientific names being ascribed to this species. In the Mediterranean Sea, and elsewhere in its range, this species was previously referred to as C. granulosus (Bloch & Schneider, 1801). The first paper in this revision series clarified that C. granulosus refers to a much larger species of gulper shark which attains at least 1.7 m length and is absent from the Mediterranean Sea. Further complicating the nomenclature of this species is the fact that the original description clearly refers to a Squalus species, and not a Centrophorus species. In this third part of the revision of the genus Centrophorus, this problematic species is redescribed. A detailed synonymy is provided and it is confirmed that C. machiquensis, C. bragancae and C. zeehaani are junior synonyms of this species. To preserve nomenclatural stability within the genus, the name Centrophorus uyato is retained for this species with a neotype from close to the original type locality off Italy being designated. Intraspecific variation within Centrophorus uyato is also discussed, particularly relating to denticle morphology and body morphology.